Melt polymerization method of liquid crystal elastomer with wide process window
By using a thermal latent catalyst during the melt polymerization of liquid crystal elastomer, the problem of uncontrollable reaction of the catalyst at high temperatures is solved, the low viscosity retention time at low temperatures is extended, the processing technology window is broadened, and processing efficiency and flexibility are improved.
Patent Information
- Application Number
- CN202411637312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing catalysts to achieve controllable reactions during the melt polymerization of liquid crystal elastomers, resulting in the impact of material quality and performance.
A thermal latent catalyst is used that promotes the Michael addition reaction between the acrylate and the thiol group under high temperature conditions, and its catalytic activity is inhibited at low temperatures.
Through this design, the low viscosity holding time of the liquid crystal elastomer at low temperatures is extended, the processing technology window is widened, the precise control of polymerization reaction is achieved, and the processing efficiency and flexibility are significantly improved.
Smart Images

Figure CN119751725A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of liquid crystal elastomer materials, in particular to a liquid crystal elastomer melt polymerization method with a wide process window. Background Art
[0002] Liquid crystal elastomers are a type of stimuli-responsive smart materials that combine the anisotropy of liquid crystal molecules with the elasticity of rubber networks. When subjected to external stimuli (such as heat, light, electricity, magnetism, etc.), these materials can undergo reversible deformation, and their unique properties make them widely used in the fields of optical materials, touch displays, actuators, soft robots, etc. The stimuli-responsiveness of liquid crystal elastomers stems from the phase transition that the material undergoes under external stimuli, that is, the reversible deformation that occurs during the transition from the liquid crystal phase to the isotropic phase.
[0003] Among the numerous liquid crystal elastomer formulations, acrylate and mercapto systems are widely used due to their efficient and stable cross-linked networks. With the emergence of commercial liquid crystal monomers, this system not only provides excellent mechanical properties and flexible formulation design, but also has adjustable reaction conditions and superior optical properties, making it suitable for a variety of applications.
[0004] Melt polymerization is an effective method for preparing acrylate-thiol system liquid crystal elastomers, which avoids the use of solvents and thus produces more uniform and excellent materials. In this process, the polymerization of acrylate and thiol usually requires the use of additives, including photoinitiators, thermal initiators and alkaline catalysts. Photoinitiators and thermal initiators are mainly used to promote click chemistry reactions between thiol and double bonds. However, the photoinitiator method is difficult to use for the preparation of bulk materials due to poor light transmittance; thermal initiators often need to be operated under an inert atmosphere, and the conditions are relatively harsh. Alkaline catalysts achieve crosslinking by promoting the Michael addition reaction between acrylate and thiol, requiring the catalyst to be evenly dispersed in the monomer to ensure the homogeneity of the material. However, since the melt polymerization process is carried out at high temperature, alkaline catalysts are prone to early gelation of the precursor, resulting in uneven dispersion of the catalyst and a large number of bubbles and defects in the final material, affecting the quality and performance of the material.
[0005] Therefore, there is an urgent need for a liquid crystal elastomer material with a wide process window during melt polymerization. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The present invention aims to solve the problem that it is difficult to achieve controllable reaction in the melt polymerization process of liquid crystal elastomers with existing catalysts. To this end, a thermal latent catalyst is proposed, which is suitable for the melt polymerization reaction of liquid crystal elastomers. The catalyst can effectively promote the Michael addition reaction between acrylate and mercapto under high temperature conditions, while at low temperatures, its catalytic activity is inhibited, showing no catalytic effect. Through this design, the low viscosity retention time of liquid crystal elastomers at low temperatures can be extended and the processing window can be widened, thereby achieving precise control of the polymerization reaction and significantly improving processing efficiency and flexibility.
[0007] In one aspect of the present invention, the present invention provides a latent catalyst. According to an embodiment of the present invention, the latent catalyst has a structure as shown in formula (I):
[0008]
[0009] The catalyst can effectively promote the Michael addition reaction between acrylate and mercapto under high temperature conditions, but its catalytic activity is inhibited at low temperatures, showing no catalytic effect. Through this design, the low viscosity retention time of liquid crystal elastomers at low temperatures can be extended and the processing window can be widened, thereby achieving precise control of the polymerization reaction and significantly improving processing efficiency and flexibility.
[0010] In another aspect of the present invention, the present invention also proposes a method for preparing a latent catalyst. According to an embodiment of the present invention, the method comprises:
[0011] Tetramethylguanidine and sodium tetraphenylborate are reacted to obtain a latent catalyst, wherein the latent catalyst has a structure as shown in formula (I),
[0012]
[0013] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0014] According to an embodiment of the present invention, the molar ratio of tetramethylguanidine to sodium tetraphenylborate is 1:(1-1.2).
[0015] According to an embodiment of the present invention, the tetramethylguanidine is pre-dissolved in a 10% hydrochloric acid aqueous solution.
[0016] According to an embodiment of the present invention, the usage ratio of the tetramethylguanidine and the 10% hydrochloric acid aqueous solution is 0.58 g:25 mL.
[0017] According to an embodiment of the present invention, the sodium tetraphenylborate is pre-dissolved in an aqueous solution.
[0018] According to an embodiment of the present invention, the usage ratio of the sodium tetraphenylborate and the aqueous solution is 1.78 g:25 mL.
[0019] According to an embodiment of the present invention, the reaction time is 1.5 hours.
[0020] According to an embodiment of the present invention, the reaction temperature is room temperature.
[0021] According to an embodiment of the present invention, the reaction further includes post-treatment and recrystallization treatment.
[0022] According to an embodiment of the present invention, the solvents for the recrystallization treatment are methanol and chloroform.
[0023] According to an embodiment of the present invention, the usage ratio of methanol to chloroform is 4:1.
[0024] In another aspect of the present invention, the present invention further provides a method for preparing a liquid crystal elastomer. According to an embodiment of the present invention, the method comprises:
[0025] Performing a first mixing process on the liquid crystal monomer, the chain extender, the cross-linking agent and the polymerization inhibitor to obtain a first mixed solution;
[0026] The latent catalyst described above or the latent catalyst obtained according to the method described above is added to the first mixed liquid, and a second mixing treatment and a curing treatment are performed to obtain a liquid crystal elastomer.
[0027] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0028] According to an embodiment of the present invention, the liquid crystal monomer is selected from 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 1,4-bis-[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene, (4-(((4-(acryloxy)butoxy)carbonyl)oxy)benzoic acid 2-methyl-1,4-diphenol ester, 2-methyl-1,4-phenylene bis(4-(4-(acryloxy)butoxy)benzoate), (3R,3AR,6S,6AR)-hexahydrofuran [3,2- B] furan-3,6-diylbis(4-((acryloyloxy)butoxy)carbonyl)oxy)benzoyl)oxy)benzoate), 4-cyanophenyl 4'-(6-acryloyloxyhexyloxy)benzoate, 4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]benzoic acid 4-methoxyphenyl ester, 4-[4-[(1-oxo-2-propenyl)oxy]butoxy]-benzoic acid biphenyl-4-yl ester or 4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]-benzoic acid 4-ethylphenyl ester.
[0029] According to an embodiment of the present invention, the chain extender is selected from 2,2'-(1,2-ethylenedioxy)bisethanethiol, 2,4-bis(hydrogen mercaptomethyl)-1,3,5-trimethylbenzene, mercapto-polyethylene glycol-mercapto, ethylene glycol bisthioacetate, di(thioglycolic acid)-1,4-butylene glycol, bis(3-mercaptopropionic acid)ethylene glycol, bis(2-mercaptoethyl) ether, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol or 1,10-decanedithiol.
[0030] According to an embodiment of the present invention, the crosslinking agent is selected from pentaerythritol tetrathioglycolate, trimethylolpropane tris(thioglycolate), (mercaptopropyl)methylsiloxane homopolymer, 1,2,4,5-benzene tetramercapto or inositol hexa(mercaptopropionate).
[0031] According to an embodiment of the present invention, the polymerization inhibitor is selected from 2,6-di-tert-butyl-p-cresol.
[0032] According to an embodiment of the present invention, the molar ratio of the acrylic acid double bonds contained in the liquid crystal monomer to the mercapto groups in the chain extender is 1:1.
[0033] According to an embodiment of the present invention, the amount of the polymerization inhibitor used is 0.5 wt % of the total mass of all raw materials in the first mixing process.
[0034] According to an embodiment of the present invention, the first mixing process is performed at a temperature of 70-90° C. (eg, 70° C., 80° C. or 90° C., etc.).
[0035] According to an embodiment of the present invention, the amount of the latent catalyst is 0.5-2wt% (eg 0.5wt%, 1wt%, 1.5wt% or 2wt%, etc.) of the total mass of all raw materials in the second mixing process.
[0036] According to an embodiment of the present invention, the curing process is performed in a vacuum drying oven.
[0037] According to an embodiment of the present invention, the temperature of the curing treatment is 100-120° C. (eg, 100° C., 110° C. or 120° C., etc.).
[0038] According to an embodiment of the present invention, the curing treatment time is 24-48 hours (eg, 24 hours, 28 hours, 35 hours, 40 hours or 48 hours, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0040] Figure 1Synthesis route of latent catalyst TPB-TMG;
[0041] Figure 2 H NMR spectrum of latent catalyst TPB-TMG;
[0042] Figure 3 Viscosity change diagram of the monomer mixture containing latent catalyst TPB-TMG and triethylamine. DETAILED DESCRIPTION
[0043] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0044] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0045] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0046] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0047] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0048] Example 1. Preparation of latent catalyst TPB-TMG
[0049] Synthesis route such as Figure 1 shown.
[0050] Tetramethylguanidine (TMG, 5.0mmol, 0.58g) was dissolved in 25mL of 10% hydrochloric acid aqueous solution. Subsequently, an aqueous solution (25mL) of sodium tetraphenylborate (5.2mmol, 1.78g) was added dropwise under vigorous stirring, and a white precipitate was immediately produced. After stirring at room temperature for 1.5 hours, the crude precipitate was filtered and washed three times with water, and the last time with methanol. Recrystallization from a 4:1 mixture of methanol and chloroform produced colorless cubic crystals, which were dried in vacuo. NMR characterization was performed using DMSO-d6 as the solvent. By Figure 2 Shown 1 It can be seen from the H-NMR spectrum that the target latent catalyst TPB-TMG was obtained in this example.
[0051] Example 2: Melt Polymerization of Liquid Crystalline Elastomer Containing Latent Catalyst
[0052] 1. Melt polymerization of liquid crystal elastomer containing latent catalyst TPB-TMG
[0053] Liquid crystal monomer (1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 5.8860 g, 10 mmol), chain extender (2,2'-(1,2-ethylenedioxy)bis(thio)thiol, 1.5951 g, 8.75 mmol), crosslinker (trimethylolpropane tris(thioglycolic acid), 0.3321 g, 0.83 mmol) and inhibitor (2,6-di-tert-butyl-p-cresol, 0.039 g, 0.5 wt% of the total mass) were added to a vial and heated at 80°C until the monomer melted and became clear and transparent. Subsequently, a thermal latent catalyst (TPB-TMG, 0.078 g, 1.0 wt% of the total mass) was added and mixed until the solution became clear and transparent again. The mixture was transferred to a specific mold and cured in a vacuum drying oven (120°C, 24 hours). After the curing was completed, the sample was removed from the mold to obtain a liquid crystal elastomer sample.
[0054] 2. Melt polymerization of liquid crystal elastomer containing catalyst triethylamine
[0055] Liquid crystal monomer (1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 5.8860 g, 10 mmol), chain extender (2,2'-(1,2-ethylenedioxy)bisethanethiol, 1.5951 g, 8.75 mmol), crosslinker (trimethylolpropane tris(thioglycolic acid), 0.3321 g, 0.83 mmol) and inhibitor (2,6-di-tert-butyl-p-cresol, 0.039 g, 0.5 wt% of the total mass) were added to a vial and heated at 80°C until the monomer melted and became clear and transparent. Subsequently, a catalyst (triethylamine, 0.078 g, 1.0 wt% of the total mass) was added and mixed until the solution became clear and transparent again. The mixture was transferred to a specific mold and cured in a vacuum drying oven (120°C, 24 hours). After the curing was completed, the sample was removed from the mold to obtain a liquid crystal elastomer sample.
[0056] Example 3: Study on widening the processing window
[0057] The viscosity of the two mixtures after adding the catalyst in Example 2 was tested (80°C) to study whether the latent catalyst has the effect of expanding the processing window of the liquid crystal elastomer by observing the change of viscosity over time. Figure 3As shown in the figure, for the triethylamine mixture, after 1200 seconds, the viscosity of the mixture increases rapidly. For the latent catalyst TPB-TMG mixture, after 2500 seconds of heating, the viscosity of the mixture increases slowly. This shows that the latent catalyst TPB-TMG is beneficial to prolong the low viscosity retention time of the liquid crystal elastomer at low temperature and broaden the processing window.
[0058] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0059] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A latent catalyst, characterized in that: Having a structure as shown in formula (I):
2. A method for preparing a latent catalyst, characterized in that: include: Tetramethylguanidine and sodium tetraphenylborate are reacted to obtain a latent catalyst, wherein the latent catalyst has a structure as shown in formula (I), 3. The method according to claim 2, characterized in that The molar ratio of tetramethylguanidine to sodium tetraphenylborate is 1:(1-1.2); Optionally, the tetramethylguanidine is pre-dissolved in a 10% hydrochloric acid aqueous solution; Optionally, the dosage ratio of the tetramethylguanidine and the 10% hydrochloric acid aqueous solution is 0.58 g: 25 mL; Optionally, the sodium tetraphenylborate is pre-dissolved in an aqueous solution; Optionally, the usage ratio of the sodium tetraphenylborate and the aqueous solution is 1.78 g:25 mL.
4. The method according to claim 2, characterized in that: The reaction time is 1.5 hours; Optionally, the reaction temperature is room temperature; Optionally, the reaction further includes post-treatment and recrystallization treatment; Optionally, the solvent for the recrystallization treatment is methanol and chloroform; Optionally, the ratio of methanol to chloroform is 4:
1.
5. A method for preparing a liquid crystal elastomer, characterized in that: include: Performing a first mixing process on the liquid crystal monomer, the chain extender, the cross-linking agent and the polymerization inhibitor to obtain a first mixed solution; The latent catalyst according to claim 1 or the latent catalyst obtained according to any one of claims 2 to 4 is added to the first mixed liquid, and a second mixing treatment and a curing treatment are performed to obtain a liquid crystal elastomer.
6. The method according to claim 5, characterized in that The liquid crystal monomer is selected from 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 1,4-bis-[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene, (4-(((4-(acryloxy)butoxy)carbonyl)oxy)benzoic acid 2-methyl-1,4-diphenol ester, 2-methyl-1,4-phenylene bis(4-(4-(acryloxy)butoxy)benzoate), (3R,3AR,6S,6AR)-hexahydrofuran[3,2-B]furan- 3,6-diylbis(4-((acryloyloxy)butoxy)carbonyl)oxy)benzoyl)oxy)benzoate), 4-cyanophenyl 4'-(6-acryloyloxyhexyloxy)benzoate, 4-methoxyphenyl 4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]benzoate, 4-[4-[(1-oxo-2-propenyl)oxy]butoxy]-benzoic acid biphenyl-4-yl ester or 4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]-benzoic acid 4-ethylphenyl ester; Optionally, the chain extender is selected from 2,2'-(1,2-ethylenedioxy)bisethanethiol, 2,4-bis(mercaptomethyl)-1,3,5-trimethylbenzene, mercapto-polyethylene glycol-mercapto, ethylene glycol bisthioglycolate, bis(thioglycolate)-1,4-butylene glycol, bis(3-mercaptopropionic acid)ethylene glycol, bis(2-mercaptoethyl) ether, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol or 1,10-decanedithiol; Optionally, the crosslinking agent is selected from pentaerythritol tetrathioglycolate, trimethylolpropane tris(thioglycolate), (mercaptopropyl)methylsiloxane homopolymer, 1,2,4,5-benzene tetramercapto or inositol hexa(mercaptopropionate); Optionally, the polymerization inhibitor is selected from 2,6-di-tert-butyl-p-cresol.
7. The method according to claim 5, characterized in that The molar ratio of the acrylic acid double bonds contained in the liquid crystal monomer to the mercapto groups in the chain extender is 1:1; Optionally, the amount of the polymerization inhibitor used is 0.5 wt % of the total mass of all raw materials in the first mixing process.
8. The method according to claim 5, characterized in that The first mixing process is carried out at a temperature of 70-90°C.
9. The method according to claim 5, characterized in that The amount of the latent catalyst used is 0.5-2 wt % of the total mass of all raw materials in the second mixing process.
10. The method according to claim 5, characterized in that The curing process is carried out in a vacuum drying oven; Optionally, the curing temperature is 100-120°C; Optionally, the curing treatment time is 24-48 hours.
Citation Information
Patent Citations
High-temperature-resistant UV (ultraviolet) photocuring adhesive composition and application thereof
CN114702921A
Photocurable composition, cured product, laminate, method for producing cured product, and method for producing lens
CN118076660A
Liquid crystal elastomer composition and preparation method thereof
CN118126725A
Catalyst for promoting reduction of invalid liquid crystal elastomer and method for reducing invalid liquid crystal elastomer
CN118146508A